Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand. Issue 1 (2nd January 2023) - Balci, Muharrem; Rhodes, Lesley L.; Nishimura, Tomohiro; Murray, J. Sam; Harwood, D. Tim; MacKenzie, A. Lincoln; Bui, Tony; Moisan, Catherine; Thompson, Lucy; Smith, Kirsty F.
ABSTRACT: Molecular-based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium -like cells were analysed using an Amphidomataceae real-time PCR assay. Nineteen samples were positive, and 24 Azadinium -like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real-time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species-specific real-time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography-tandem mass spectrometry (LC-MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio-temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.